RETAIL GREEN SUKUK: DSN MUI FATWA AND MAQASHID SHARIA REVIEW - Risyda Nurul Qolbi; Hidayat; Umi Khusnul Khotimah (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2026)
Indonesia has significant potential to develop Retail Green Sukuk, especially in addressing climate change issues towards a green and sustainable economy. This research aims to analyze the practice, sharia compliance based on DSN-MUI Fatwa No: 137/DSN-MUI/IX/2020 on Sukuk, and maqāṣid asy-Syarī’ah review of the issuance, use of proceeds, and payment of yields (coupons) for Retail Green Sukuk, with a case study on Sukuk Tabungan Series. The research method used is field research with a qualitative case study approach, utilizing an empirical normative and maqāṣid asy-Syarī’ah (kulliyat as-Sitt) perspective. Qualitative data sources include in-depth interviews with DSN-MUI, document studies on the issuance of Sukuk Tabungan Series, and other supporting data such as regulations, fatwas, literature, and other sources related to green sukuk and maqāṣid asy-Sharī’ah issues, which are then analyzed using inductive analysis techniques. This study finds that the practice of Retail Green Sukuk Sukuk Tabungan Series complies with the DSN-MUI Fatwa No: 137/DSN-MUI/IX/2020 concerning Sukuk. However, sharia compliance in its operations needs to be enhanced and explored further so that the practice of Retail Green Sukuk in Indonesia, particularly Sukuk Tabungan Series, can be carried out completely in accordance with sharia principles. The idea of 'umum al-balwa’ can be used in conjunction with the fiqh principle مَا لَا يُدْرَكُ كُلُّهُ لَا يُتْرَكُ كُلُّهُ. The process of issuance, use of proceeds, and payment of yields (coupons) for Retail Green Sukuk Sukuk Tabungan Series not only fulfills the objectives of maqāṣid asy-Syarī’ah (hifẓ ad-Dīn, hifẓ an-Nafs, hifẓ al-‘Aql, hifẓ an-Nasl, hifẓ al-Māl, and hifẓ al-Bīah), but also contributes to the sustainable economy and the welfare of society.